2012
DOI: 10.1051/matecconf/20120201010
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Jorf Lasfar fly ash as an additive to cement

Abstract: Abstract:Recycling fly ash is a good example of valorization of waste. It gives a solution the environmental problem by avoiding land filling, and reducing CO2 emission in the atmosphere. In this work we studied the physical-chemical characteristics of Jorf Lasfar fly ash. The parameters investigated were particle size, density, specific surface Blaine, chemical and mineralogical compositions. The techniques used are scanning electronic microscope (SEM), transmission electronic microscope (TEM), X-rays fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
1
3
0
Order By: Relevance
“…Besides, the compressive strength decreases with the addition of fly ash (Figure 3). These results are in agreement with other studies [23,25], who found that the compressive strength decreases for additions of 5%, 10% and 20% of fly ash, and goes below the cement control values at an addition rate of 7%. This is due to the fact that class F fly ash is a slow reacting pozzolan, which means that it only starts to react noticeably after several weeks at 20°C of curing [26].…”
Section: Cmss-2017supporting
confidence: 93%
See 1 more Smart Citation
“…Besides, the compressive strength decreases with the addition of fly ash (Figure 3). These results are in agreement with other studies [23,25], who found that the compressive strength decreases for additions of 5%, 10% and 20% of fly ash, and goes below the cement control values at an addition rate of 7%. This is due to the fact that class F fly ash is a slow reacting pozzolan, which means that it only starts to react noticeably after several weeks at 20°C of curing [26].…”
Section: Cmss-2017supporting
confidence: 93%
“…When unmilled FA was added to the cement, the refusal increased reaching 12.2% and 3.6% for 45 and 80µm sieves respectively. This increase was also noticed when different percentages (3, 5, 7 and 10%) of unmilled FA were added to the cement [23]. On the other hand, when the cement was blended with milled FA, the refusal of the samples was kept the same as the reference.…”
Section: Physical and Chemical Characteristicsmentioning
confidence: 75%
“…Analysis by scanning electron microscopy was performed to determine the morphology and the microstructure of the phases that constitute the sample of fly ash [13] and bottom ash used as an additive to CPJ 45 cement.…”
Section: Scanning Electron Microscopy (Sem) Coupled With Chemical Anamentioning
confidence: 99%
“…Beyond this value we see respectively a gradual decrease of resistances with 20% of fly ash 33.3 MPa and 6.5 MPa for compressive and bending strength. Nabih et al have studied the influence of the addition with different percentage of fly ash on the mechanical properties of the clinker, and they reported that the compression and bending resistances for these mixtures went through a maximum at 28 days with the addition of 7% (by weight) of fly ash [13,15] Al Hamaniedh and all have studied the compressive strength of a series of cement prepared by addition of Jordan oil shale ash, and they found that the best mechanical resistance to compression is marked for cement prepared with 10% of ash [16]. In our case we observe a slight decrease of resistance with the addition of 5% of oil shale ash, followed by a gradual increase which peaked at 10%, with 42.7 MPa for the compressive strength and 7.3 MPa for the bending one.…”
Section: Mechanical Proprietiesmentioning
confidence: 99%